A Novel Dual-Polarization Total Power Radiometer with Single Channel. (13th February 2014) - Niu, Yiming; Cui, Can; Yang, Guo; Wu, Wen
Abstract : A dual-polarization total power millimeter wave (MMW) radiometer with single channel was proposed in this paper. It completed the subtraction of two orthogonally polarized signals in the RF front end. The system used one channel to achieve the function of two channels. On the basis of discussing the theory and the configuration of the system, the performance of the system and the ability to identify the false target were analyzed and simulated. The results showed the radiometer could solve the problem that the performance of dual-polarization radiometer becomes weak because of gain inconformity with two channels. The system was cheap and small and could identify the false target which has different apparent temperatures at vertical- and horizontal-polarized radiations.